Reliability and Economic Analysis of a Modular Converter With Three Vienna Converters Connected in Parallel - Jae-Seong Jo; Sang-Hyeok Lee; Guangxu Zhou; Feel-Soon Kang (IEEE Access)
This paper analyzes the reliability of a 90kW modular converter with three Vienna converters in parallel modules. We designed a Markov model for partial failures and analyzed reliability for a configuration where each module has 30 kW without redundancy and a configuration where each module has 45 kW and 90 kW with redundancy. In the case of 45kW and 90kW modules with redundancy effects, if a failure occurs in any of the three parallel modules, the module that can operate normally will share the power of the failed module. Therefore, the current stress applied to the components of the Vienna converter increases, and the junction temperature of the switching devices increases, which raises the failure rate of the Vienna converter. This paper improves the accuracy of reliability analysis by reflecting the increase in failure rate according to the operating temperature of the components when the Vienna converter operates under maximum load conditions. Simulations are performed for various partial failure conditions, and Markov models and cost models are designed to analyze the correlation between reliability and price according to the redundancy effect. The redundancy effect due to module margin increases the mean time to failure (MTTF) by up to 4.6 times. However, it should be noted that when each Vienna converter module is designed as 90kW, the cost increases by USD 253 compared to when it is intended as 30kW.